An Intrinsic Flame‐Retardant Organic Electrolyte for Safe Lithium‐Sulfur Batteries. Issue 3 (13th December 2018) - Yang, Huijun; Guo, Cheng; Chen, Jiahang; Naveed, Ahmad; Yang, Jun; Nuli, Yanna; Wang, Jiulin
Abstract: Safety concerns pose a significant challenge for the large‐scale employment of lithium–sulfur batteries. Extremely flammable conventional electrolytes and dendritic lithium deposition cause severe safety issues. Now, an intrinsic flame‐retardant (IFR) electrolyte is presented consisting of 1.1 m lithium bis(fluorosulfonyl)imide in a solvent mixture of flame‐retardant triethyl phosphate and high flashpoint solvent 1, 1, 2, 2‐tetrafluoroethyl‐2, 2, 3, 3‐tetrafluoropropyl (1:3, v/v) for safe lithium–sulfur (Li−S) batteries. This electrolyte exhibits favorable flame‐retardant properties and high reversibility of the lithium metal anode (Coulombic efficiency >99 %). This IFR electrolyte enables stable lithium plating/stripping behavior with micro‐sized and dense‐packing lithium deposition at high temperatures. When coupled with a sulfurized pyrolyzed poly(acrylonitrile) cathode, Li−S batteries deliver a high composite capacity (840.1 mAh g −1 ) and high sulfur utilization of 95.6 %. Abstract : Fireproof : An intrinsic flame‐retardant (IFR) electrolyte was developed to address safety concerns of Li−S batteries. The IFR electrolyte enabled high reversibility and stability of Li. Unique electrode interphases led to micro‐sized Li deposition and high‐performance Li−S batteries at high temperatures.